Seasonality in house prices - Florian Kajuth; Tobias Schmidt (Deutsche Bundesbank, 2011)
The contribution of this paper is to offer a rationale for the observed seasonal pattern in house prices. We first document seasonality in house prices for the US and the UK using formal statistical tests and illustrate its quantitative importance. In the second part of the paper we employ a standard model of dynamic optimisation with housing demand and seasonal shocks in non-durables in order to characterise seasonality in house prices as an equilibrium outcome. We provide empirical evidence for seasonality in house prices with our small model using US and UK data.
Keywords: D91; R21; R31; 330; house prices; seasonality; optimal housing consumption